2014
DOI: 10.1016/j.toxlet.2014.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Single-walled carbon nanotube exposure induces membrane rearrangement and suppression of receptor-mediated signalling pathways in model mast cells

Abstract: Carbon nanotubes (CNT) are environmental challenges to the respiratory and gastrointestinal mucosa, and to the dermal immune system. Mast cells (MC) are pro-inflammatory immunocytes that reside at these interfaces with the environment. Mast cells are sources of pro-inflammatory mediators (histamine, serotonin, matrix-active proteases, eicosanoids, prostanoids, cytokines and chemokines), which are released in a calcium-dependent manner following immunological challenge or physico-chemical stimulation. Since C-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Such an observation is intriguing in that the dissolution of C20 is expected to be much slower than P20 eliminating Ag + as a possible cause for degranulation (Kittler et al, 2010). These findings are consistent with other reports that the uptake of NPs by mast cells causes a variety of mast cell responses including the suppression of mast cell degranulation and decreased reactive oxygen species generation while some have been shown to induce degranulation (Dellinger et al, 2010; Ryan et al, 2007; Umemoto et al, 2014). Our findings suggest cellular signaling initiated by size-dependent NP-cell surface receptor interactions facilitated mast cell degranulation that is not completely driven by NP uptake.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Such an observation is intriguing in that the dissolution of C20 is expected to be much slower than P20 eliminating Ag + as a possible cause for degranulation (Kittler et al, 2010). These findings are consistent with other reports that the uptake of NPs by mast cells causes a variety of mast cell responses including the suppression of mast cell degranulation and decreased reactive oxygen species generation while some have been shown to induce degranulation (Dellinger et al, 2010; Ryan et al, 2007; Umemoto et al, 2014). Our findings suggest cellular signaling initiated by size-dependent NP-cell surface receptor interactions facilitated mast cell degranulation that is not completely driven by NP uptake.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, carbon based NPs have been reported to induce mast cell activation as reported with multi-walled carbon nanotubes or can suppress mast cell activation as it has been reported with single-walled carbon nanotubes and fullerene C 60 (Huang et al, 2009; Katwa et al, 2012; Ryan et al, 2007; Umemoto et al, 2014). Based on our current findings, mast cell degranulation is not entirely dependent on internalization of the NP.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, analysis showed that internalization of SWCNTs could activate different cellular mechanisms from ROS generation (Aldieri et al, 2013; Jaeger et al, 2012) to inflammation (van Berlo et al, 2014), cell signaling (Ellinger-Ziegelbauer and Pauluhn, 2009), protein expression (Lai et al, 2013), fibrogenesis (Muller et al, 2005; Porter et al, 2010), cellular attachment (Kaiser et al, 2013), viability (Cui et al, 2005) or proliferation (Müller et al, 2011), with such effects being dependent on the length (Manke et al, 2014; Sato et al, 2005), agglomeration (Wick et al, 2007), and surface chemistry (Jiang et al, 2009; Liu et al, 2014) of the nanotubes being tested. However, such methods failed to interpret intermediate exposure time points and mostly defined SWCNT-induced toxicity as invasive cellular changes reflected by cytoskeletal rearrangement (Umemoto et al, 2014), membrane disruption (Chang and Violi, 2006; Umemoto et al, 2014), disruption of the mitotic spindle (Sargent et al, 2012b) and cellular aneuploidy (Sargent et al, 2009; Siegrist et al, 2014), just to name a few.…”
Section: Discussionmentioning
confidence: 99%
“…A higher internalization could occur for the 6 h treated SWCNTs relative to both 3 h treated and pristine SWCNTs as reflected by the higher changes in both the resistance and cell adhesion properties. Based on the known interactions of the internalized nanotubes with the cytoskeletal elements, as well as cytoskeleton’s role to regulate cell–substrate interactions (Holt et al, 2010; Umemoto et al, 2014), the regained adhesion characteristics observed after 48 h of exposure to 6 h treated SWCNTs could be associated with reduced cellular toxicity of these nanotubes. Complementary, changes in cellular adhesion could be associated with changes in cellular morphology (Song et al, 2013) and elasticity (Dong et al, 2014, 2013b), which in turn could influence cellular viability.…”
Section: Discussionmentioning
confidence: 99%
“…104 SWCNTs can form large aggregates (micrometers in diameter) in cell culture medium or inside the cell body. 105 Umemoto and coworkers 106 From these studies, it clearly appears that aggregation of SWCNTs should be avoided and that nanotube individualization is a key parameter to minimize cellular toxicity.…”
Section: Aggregationmentioning
confidence: 99%